Multinational corporate strategy and finance - Molyneux, Philip; Institute of Financial Services (Great Britain) (Canterbury, England : Institute of Financial Services, 2004)
Helps understand the strategic and financial needs and problems of international and multinational corporate groups and to identify and apply ways in which these needs can be met through the bank and capital markets. It enables the understanding of corporate strategy and business analysis as well as the bank's lending services, cross-border risks, examination of capital markets and capital treasury management.
Includes bibliographical references and index.
oif 21/07/14; osa 21/07/14
Loans
Keywords: International business enterprises -- Finance; Strategic planning; Business planning